ANALISIS KINERJA KEUANGAN DENGAN RASIO LIKUIDITAS DAN SOLVABILITAS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jayanti Oktavia Sunardianti; Fikri Jajang (STIE Indonesia Malang, 2021)
This study aims to analyze financial performance as seen from the Liquidity and Solvency Ratios in Food and Beverage companies listed on the Indonesia Stock Exchange in the 2017 - 2019 period. from 2017 to 2019. The sample in this study was selected based on the purposive sampling technique of collecting samples by considering certain criteria that have been made for objects that are in accordance with the research objectives. The samples in this study were 5 food and beverage companies listed on the Indonesia Stock Exchange for the period 2017-2019.The results show that the overall average current ratio from 2017 to 2019 with a value of 3.99 is said to be liquid. Overall, the average quick ratio from 2017 to 2019 with a value of 3.04 is said to be liquid. Overall, the average debt to assets ratio from 2017 to 2019 which has the same value of 0.50 is said to be Solvabel. Solvabel said that the average debt to equity ratio from 2017 to 2019 was 1.12 because short-term debt is greater than long-term debt.Keyword. Financial performance, liquidity ratio, solvability ratio, food and beverage